Albumy Modrzejewskiej. Scrapbook jako ulotny dokument osobisty w drugiej połowie XIX wieku .......... 101 („Szalony, kto nie chce wyżej, jeżeli może”: Studia i materiały do badań nad życiem i twórczością Heleny Modrzejewskiej, 2025)
MODJESKAS ALBUMS: THE SCRAPBOOK AS AN EPHEMERAL PERSONAL DOCUMENT IN THE SECOND HALF OF THE 19TH CENTURYIn the second half of the 19th century, scrapbooks were very popular in America, the renaissance of which can be observed today. Among the many genres of scrapbooks, one can find specialised albums dedicated to theatre, or even just to a single artist. The aim of this article is to analyse selected scrapbooks dedicated to Helena Modjeska and to identify those of their genre characteristics that would allow them to be described as ephemeral personal documents.